PENGARUH PERTUMBUHAN PERUSAHAAN FINANCIAL TECHNOLOGY TERHADAP KINERJA PERBANKAN - Mauline, Riesti; Satria, Dias (Contemporary Studies in Economic, Finance and Banking, 2022)
The purpose of this study was to determine the effect of the growth of fintech companies on bank performance. The researcher expands the analysis by looking at the difference in influence between State-Owned Commercial Banks (BUMN) and Regional Development Banks (BPD) in this relationship and uses a sample of 17 banks that are included in the list of Conventional Banks in Indonesia in the 2011–2020 period. The researcher found a negative and significant relationship between the growth of FinTech firms and bank performance for both groups of banks. In addition, the researcher tested the hypothesis through several additional tests and robustness tests, such as the GMM. The findings of this study may be relevant for banks, policy makers and academic research.